DIE ROL VAN DIE SEEMAG IN DUITS SUIDWES-AFRIKA 1914-15 - Grobler, J.E.H. (Scientia Militaria - South African Journal of Military Studies, 2012)
At the outbreak of World War I the German colony of South West Africa poseda serious threat to the British war effort.’ The colony wn situated on the main andsefest British supply and communication route to the eut, and It was therefore of theutmost Importance that It should fall Into Allied hands. Otherwise the harbours ofUideritzbucht, Walflsch Bay and Swakopmund might be used by the German Pacificsquadron - then operating off the South American Cont, and strong radio transmittersof the colony could keep the German High Command well Informed of the situationIn the southern hemisphere. General Botha, Prime Minister of the Union of South Africa, agreed to a Britishrequest to send an expedition against the German colony, but before this could getunder way, a serious rebellion broke out In the Union. The defeat of Cradock’s squadronat Coronel and the prnenca of von Spee’s warships in the Atlantic added to theanxietln of the South African leaders. For the next two months the Admiralty’. Inability to provide an adequate escortfor the expeditionary foree and the dlaorganlaetlon of the Union Defence Forenby the rebellion upset the South African plans for the campaign In South West Africa.Only with the defeat of von Spee at the Falkland Islands and the capitulation of theprincipal rebel forees In South Africa was It possibleto launch the expedition effectively.